Reply to ‘Evidence for simple volcanic rifting not complex subduction initiation in the Laxmi Basin’ - Dhananjai K. Pandey (Nature Portfolio, 2020)
Recently, Pandey et al. proposed relict subduction initiation occurred along a passive margin in the northwest Indian Ocean, however, Clift et al. questioned their evidence for subduction initiation, suggesting that simpler rifting-related processes could more simply explain the available data. Here, Pandey et al. reply to Clift et al.’s comment, and argue that geochemical and isotope data for Laxmi basin lavas distinctly imply relict subduction initiation.